PLIKASI SOFTWARE COURSE LAB V.2.4 UNTUK IMPLEMENTASI MODEL PEMBELAJARAN INTERACTIVE PROBLEM SOLVING PADA MATA KULIAH MATEMATIKA - Raharjo, Nuryadin Eko (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The purposes of this research are (1) to acquire the design of interactive learning media, (2) to analyze the obstacles and to find the solutions, (3) to analyze the implementation of interactive learning media model on mathematics course to improve students learning achievement. This research can be catagorized as action research with several stages: (1) problem design, (2) media design, (3) expert validation, (4) implementing interactive problem solving with CourseLab V.2.4, (5) monitoring and evaluation, (6) reflection and revision, (7) implementing the next cycle. This research was conducted in the department of civil engineering and planning Faculty of Engineering, Yogyakarta State University. The reseacrh participants were the students who joined Mathematics Data Analysis Course. Data anaysis technique were using quanitative and qualitative descriptive analysis. The findings showed that (1) the criteria for learning media design with CourseLab V.2.4 which is appropriate to implement learning model of interactive problem solving were as follow: (a) the level of difficulty was made in moderate level, (b) time allocation was implemented for the whole questions, not for every single question, (c) there was no need to show the answer key, (d) varying the type of test item, (e) there was no need to provide calculator application assistance; (2) there were some ways should be conducted to overcome the obstacles in implementing this interactive media, i.e. (a) start by publishing the software in the form of html, (b) adjusting the security setting of the browser apllication on low level, (c) using courselab program should be thoroughly because this program can save any changes automatically, (d) file should be compresed in the form of zip, rar, or the other before it was distributed to the students, (3) the implementation of CourseLab V.2.4 on learning media of interactive problem solving was effective to improve students’ learning achievement. Keywords: interactive media, interactive problem solving and mathematics.